Enhancing cell‐edge performance using multi‐layer soft frequency reuse scheme. Issue 22 (8th October 2015) - Hossain, M.S.; Tariq, F.; Safdar, G.A.
Abstract : In cellular systems, maintaining data rate at the cell edge has been a challenging task due to strong co‐channel interference from neighbouring cells. Several techniques have been proposed to tackle the issue, among which soft frequency reuse (SFR) is the most widely used. A novel multi‐layer SFR scheme combined with cell sectoring is proposed to improve the performance in cell‐edge region. Then, a spectrum allocation scheme in a three‐cell reuse system is designed to ensure the maximisation of the efficiency. A generic expression for power allocation in different regions along with the signal‐to‐noise ratio of multi‐layer SFR in sectored cell is derived. Finally, system‐level simulation has been carried out to demonstrate the efficiency of the proposed resource allocation scheme. It is shown that the spectral efficiency at cell‐edge area improves by ∼10% which is significant for the cell‐edge region.